Hot carrier extraction from plasmonic-photonic superimposed heterostructures - Lee, Sanghyuk; Yu, Sungju (Journal of Chemical Physics, 2022)
Plasmonic nanostructures have been exploited in photochemical and photocatalytic processes owing to their surface plasmon resonance characteristics. This unique property generates photoinduced potentials and currents capable of driving chemical reactions. However, these processes are hampered by low photon conversion and utilization efficiencies, which are issues that need to be addressed. In this study, we integrate plasmonic photochemistry and simple tunable heterostructure characteristics of a dielectric photonic crystal for the effective control of electromagnetic energy below the diffraction limit of light. The nanostructure comprises high-density Ag nanoparticles on nanocavity arrays of SrTiO3 and TiO2, where two oxides constitute a chemical heterojunction. Such a nanostructure is designed to form intense electric fields and a vectorial electron flow channel of Ag → SrTiO3 → TiO2. When the plasmonic absorption of Ag nanoparticles matched the photonic stopband, we observed an apparent quantum yield of 3.1 × 10-4 e- per absorbed photon. The contributions of light confinement and charge separation to the enhanced photocurrent were evaluated.
Keywords: Carrier extraction; Hot-carriers; Photo-induced; Photocatalytic process; Photochemical process; Plasmonic nanostructures; Plasmonics; Property; Resonance characteristic; Surface-plasmon resonance